1998
DOI: 10.1172/jci2723
|View full text |Cite
|
Sign up to set email alerts
|

Induction of insulitis by glutamic acid decarboxylase peptide-specific and HLA-DQ8-restricted CD4(+) T cells from human DQ transgenic mice.

Abstract: Insulin-dependent diabetes mellitus in humans is linked with specific HLA class II genes, e.g., HLA-DQA1*0301/ DQB1*0302 (DQ8). To investigate the roles of HLA-DQ8 molecules and glutamic acid decarboxylase (GAD) in disease development, we generated DQ8

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
55
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 61 publications
2
55
0
Order By: Relevance
“…The DQ8 transgenic line described here was created directly in the NOD background. Descriptions of at least two other DQ8 transgenic, IAb knockout mouse lines (and their derivatives) have been published by David and colleagues (19)(20)(21) and Wen and colleagues (22)(23)(24); those lines have been used to investigate a number of autoimmune models, particularly type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…The DQ8 transgenic line described here was created directly in the NOD background. Descriptions of at least two other DQ8 transgenic, IAb knockout mouse lines (and their derivatives) have been published by David and colleagues (19)(20)(21) and Wen and colleagues (22)(23)(24); those lines have been used to investigate a number of autoimmune models, particularly type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…Adoptive transfer of disease with GAD Recipients needed pretreatment with [58] 247-266 and 509-528 specific lines streptozotocin to generate islet insult HLA-DQB1*0302…”
Section: Gad65mentioning
confidence: 99%
“…It has, however, been shown that sufficient CD4 T cells can be selected in the thymus without human CD4, although the numbers may be lower than in in conventional mice. These T cells selected on human HLA molecules are functional in the presence of mouse CD4 and in the absence of human CD4 molecules [57,58,59,60]. Altmann and co-workers [61] directly compared immune responses in HLA transgenic mice with or without a human CD4 transgene and found that the immune responses were not significantly different in these mice.…”
Section: Do Hla Class II Transgenic Mice Develop Autoimmune Diabetes?mentioning
confidence: 99%
“…It is therefore not surprising that the HLA transgenic animals that have been studied either in the presence or absence of endogenous mouse MHC class II do not spontaneously develop the HLA-associated diseases [58,60]. This is also true when the HLA transgene is expressed on the NOD background [62] in the absence of the predisposing I-A g7 .…”
Section: Do Hla Class II Transgenic Mice Develop Autoimmune Diabetes?mentioning
confidence: 99%